Development of a demonstration motion program for Kawada dual arm industrial robot - Azhagappa, Kannan (2016)
This report aims to provide an understanding of the different ways in which a specific robot, Kawada Dual Arm Industrial Robot (Nextage Robot), can be implemented to do a set of particular task in industries and also describes about the ways in which the robot can be controlled in real time. It will also go through the advantages and disadvantages of the current planning and control methods of the robot.